2021
DOI: 10.3390/ma14154083
|View full text |Cite
|
Sign up to set email alerts
|

Economic Friendly ZnO-Based UV Sensors Using Hydrothermal Growth: A Review

Abstract: Ultraviolet (UV) sensors offer significant advantages in human health protection and environmental pollution monitoring. Amongst various materials for UV sensors, the zinc oxide (ZnO) nanostructure is considered as one of the most promising candidates due to its incredible electrical, optical, biomedical, energetic and preparing properties. Compared to other fabricating techniques, hydrothermal synthesis has been proven to show special advantages such as economic cost, low-temperature process and excellent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 117 publications
(504 reference statements)
1
20
0
Order By: Relevance
“…ZnO nanowires (ZNWs) have been extensively capitalized in various fields involving transducer, biomedical, electronic, and photonic applications because of their structural and functional versatility. ZNWs can be grown by diverse methods, such as chemical vapor deposition (CVD) based on vapor–liquid–solid (VLS) and vapor–solid (VS) mechanisms, and by a hydrothermal reaction. ,, While all of these methods are effective, hydrothermal ZNW growth has the practical advantages of low-temperature and scalable processing , compared to CVD-based growth, which requires a high-temperature furnace operation, limiting the processable substrate material and area. Some typical hydrothermal growth recipes, however, demand the high-temperature (∼300–350 °C) thermal sintering of Zn-salt-based textured ZnO seed layers prior to ZNW growth, which restricts the otherwise wider applications of substrate materials such as flexible plastics.…”
mentioning
confidence: 99%
“…ZnO nanowires (ZNWs) have been extensively capitalized in various fields involving transducer, biomedical, electronic, and photonic applications because of their structural and functional versatility. ZNWs can be grown by diverse methods, such as chemical vapor deposition (CVD) based on vapor–liquid–solid (VLS) and vapor–solid (VS) mechanisms, and by a hydrothermal reaction. ,, While all of these methods are effective, hydrothermal ZNW growth has the practical advantages of low-temperature and scalable processing , compared to CVD-based growth, which requires a high-temperature furnace operation, limiting the processable substrate material and area. Some typical hydrothermal growth recipes, however, demand the high-temperature (∼300–350 °C) thermal sintering of Zn-salt-based textured ZnO seed layers prior to ZNW growth, which restricts the otherwise wider applications of substrate materials such as flexible plastics.…”
mentioning
confidence: 99%
“…Considering the overwhelming synthesis techniques, it is found that ZnO is a very sensitive material to the synthesis technique, which leads to presenting different morphological, structural and optical properties. Another serious problem is the incorporation of different pollutants of different sizes are directly and indirectly that are inevitably incorporated into the matrix of this inorganic material [8]. Morphology is decisive and drastically governed by crystal growth parameters, in particular ZnO presents different, impressive and wonderful morphologies associated directly with the growth parameters as well as with the applied technique [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, plenty of excellent review papers have summarized the progress of ZnO-based UVPDs. [12][13][14][15][16] However, there are few reviews on other II-VI group semiconductor (ZnS, CdS, ZnSe, etc.) UVPDs.…”
Section: Introductionmentioning
confidence: 99%